A volume-preserving model for predicting the geometry of traces produced by drop-on-demand 3D printing - R. Zamora; F. Faura; J. López; J. Hernández (Materials & Design)
A model is proposed to predict the geometry of traces generated by molten metal droplet deposition on a flat solid surface. The model also allows the determination of the nozzle displacement that ensures neither droplet buildup nor printed trace discontinuity as a function of impinging droplet size and drop-to-drop and drop-to-substrate contact angles. Experiments performed with Field's alloy droplets and experiments by other authors are used to validate the model. The proposed model significantly improves the predictions for the geometry of the traces obtained using a non-volume-conservative model.